The Utilization of History Module in the Development of Multiculturalism-Based Team Games Tournament Model to Improve the Bhineka Attitudes on 10th Grade Students in SMA Erlangga Pematangsiantar - Ahmad Fakhri Hutauruk; Andres M. Ginting (Budapest International Research and Critics University, 2020)
This research is a development research that aims to produce alternative teaching materials in the form of a multiculturalism-based TGT model in increasing the diversity attitudes of students at Erlangga Pematangsiantar High School. The making of this module also aims to increase learning resources in the classroom and innovate learning media. The validation results of the module where the results of the material expert validation showed that the results of the material expert validation for the content component got an average score of 8.8 and 8.6 for the language component. The total average score for the two components was 8.7 in the “Highly Valid” category. The model's effectiveness test used a parametric statistical test, including the independent sample t test and paired sample t test. The results of the independent sample t test show that the value of tcount> ttable (3.101> 1.711) so that H0 is rejected and H1 is accepted, which indicates that there is a difference in the mean cognitive scores of the experimental and control groups. In addition, the results of the independent sample t test for the attitude scale show that the value of t count> t table (2.527> 1.711) so that H0 is rejected and H1 is accepted, which indicates that the diversity attitudes of students who use the history module are higher than students who use conventional models. The results of the calculation of the paired sample t test for the cognitive domain show that the value-tcount (-6,271) <-ttable (-1,711). H0 is rejected and H1 is accepted, so it can be seen that there is a difference in the mean score of the experimental group students before and after being treated. While the results of the calculation of the paired sample t test for the affective domain show that the value-tcount (-3,698) <-ttable (-1,711). H0 is rejected and H1 is accepted, so it can be seen that there is a difference in the level of awareness of the diversity of the experimental group students between before and after treatment. Developing a multiculturalism-based TGT model history module is able to develop students' diversity attitudes.